Patients Satisfaction Based on Corporate Entrepreneurship - Tri Ratnasaria, Ririn; Prasetyo, Ari; Kurniawati, Masmira; Fajar Cahyono, Eko (International Journal of Engineering and Technology, 2018)
This research aim to determine what factors are included in the service excellence based on corporate entrepreneurship, whether these factors affect the patient satisfaction, and which factors that influencing dominantly to patient satisfaction. The research design of this study is exploratory quantitative approach, which is conducted in two stages. The first step, the research conducted by open-ended question to explore the perception of the 40 patients about the service excellence of the hospital, so it can be known the factors which include in service excellence based on corporate enterpreneurship can be developed in the improvement of health services at the Dr. Soetomo Hospital after the implementation of BPJS, then proceed with a structure close-ended question to 400 patient of Health-BPJS. The sampling technique was by purposive non-random sampling. The result of this study are, first, factors affecting patient satisfaction of Health-BPJS participant after get treatment at the government hospital (Dr. Soetomo Hospital and Hajj Public Hospital) formed by six factors. Factors that formed was named by the reliability factor, empathy factor, the factor means of support, administrative factors, service factors, and factors of hospital hygiene.Â Second, indicators with the highest loading values obtained from the rotation calculation factors are indicators of X13 on the reliability factor is the health services infrastructure supported by sophisticated technology.Â Â